Guideline to define breeding objective functions, construct selection indexes and deal with uncertain sires in sheep and goat breeding programmes - Mueller, Joaquin Pablo; Getachew, Tesfaye; Rischkowsky, Barbara; Haile, Aynalem (ICARDA, 2023)
In three main chapters this guideline describes basic procedures to (1) define breeding objectives, (2) construct and evaluate selection indexes and (3) estimate breeding values in populations with uncertain sires. The guideline targets practical sheep and goat advisors involved in the operation of animal breeding programmes, typically community-based programmes in low input systems. In such systems multiple goal traits are aimed, selection indexes are useful and incomplete pedigrees are common. After presenting the basic theoretical background to deal with each of these issues, the procedures are explained using field examples. Spreadsheet files and computer programs are provided as supplementary material to trace the steps involved in the calculations and to facilitate the application of the procedures to user defined cases.